Investigating Digital (Dis)engagement of Open Government: Case Study of One Data Indonesia - Agie Nugroho Soegiono (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2018)
Over the last decade, Indonesia has achieved remarkable progress in promoting transparent andinclusive development through implementing open government principles. This research investigatesone of the open government projects in Indonesia- One Data Indonesia (ODI), a one-stop opengovernment data portal that provides accurate, reliable, and interoperable single-reference datafor the public to use and redistribute without any limitation. The study aims to highlight thecurrent updates on open data implementation in Indonesia and the challenges that may hinder itsapplication in future. The study is an action research, conducted through the participation of theauthor in a three-month internship programme at the Executive Office of the President Republic ofIndonesia. Data on the portal’s engagement was based on Google Analytics. This study finds thatthere is disengagement in open data implementation, which is reflected by a small percentage ofavailable datasets and an imbalance in user access across Indonesia. This study argues that thedisengagement is due to several factors, including irrelevant and uncertain regulatory frameworks,confusion over setting priority goals, inadequate data infrastructure, and limited digital-literatehuman resource. Despite high investment and expectations from the portal, the benefits and civicengagement it has generated so far remain questionable.